Active surveillance in localized prostate cancer: comparison of incidental tumours (T1a/b) and tumours diagnosed by core needle biopsy (T1c/T2a): results from the HAROW study. (23rd September 2015) - Herden, Jan; Wille, Sebastian; Weissbach, Lothar
Abstract : Objective: To conduct a comparative prospective analysis of patients with incidental T1a/T1b prostate cancer (IPCa) and those with prostate cancer (PCa) diagnosed by core needle biopsy, treated by active surveillance (AS), with regard to inclusion criteria, progression and switch to deferred treatment. Patients and Methods: The HAROW study is an observational outcomes research study on the management of localized PCa. Treating urologists reported clinical variables and information on therapy and clinical course of disease at 6‐month intervals. With respect to therapy, only recommendations were made; the final decision on the therapeutic method rested with the treating physician. Results: Out of 2 957 patients included in the HAROW study, 447 chose AS. The median follow‐up was 28.3 months. T1a, T1b, T1c and T2a disease were diagnosed in 81, 18, 292 and 56 patients, respectively. Patients in the IPCa group had lower prostate‐specific antigen (PSA) levels (4.2 vs 6.1 ng/mL) and more comorbidities than those diagnosed by core needle biospy. The IPCa group also had fewer re‐biopsies (25.3 vs 43.2%) and fewer changes to invasive treatment (12.1 vs 25.9%). No significant differences were found with respect to the criteria for discontinuation, subsequent therapies and histological findings after radical prostatectomy. Conclusion: Urologists are highly inclined to use AS as a therapeutic option in IPCa. More patients with IPCa than those diagnosed after core needle biopsy continued on AS, which was also associated with the indication for a re‐biopsy being less stringently observed.